Job Stress from Nurses’ Working Conditions in Sabah Women and Child Hospital - Duasin, Clarice; Baddiri, Baidi; Mamat, Rohani; Musa, Mazlinda; Satu, Caroline; Saat, Siti Fatimah (Universitas Muhammadiyah Surakarta, 2024)
Both excessive and insufficient workloads can cause stress among employees. It has been established that as tasks take longer to complete, employee happiness tends to decrease, which can significantly impact their overall health and mental well-being. The primary objective of this study is to examine the relationship between age and working conditions concerning job stress among registered nurses in a government hospital in Sabah. The quantitative survey approach was employed, involving 60 registered nurses with a minimum of 3 years of experience. Purposive sampling was utilized to ensure a sample that would provide comprehensive insights and discoveries into the factors influencing job stress among nurses in this specific setting. The analysis indicated that there was no statistically significant relationship between age, working conditions as demographics, and job stress (p = 0.499). The average stress level reported by respondents was 15.7 ± 2.32379 on a scale where higher scores indicate greater stress. This finding suggests that the observed demographic characteristics, including age and specific working conditions, did not correlate with higher or lower levels of job stress among the nurses surveyed. Based on the survey results, it can be concluded that age and the specific working conditions studied do not appear to significantly influence the experience of job stress among registered nurses at the government hospital in Sabah. This implies that other factors not explored in this study may have a more pronounced impact on job stress levels within this population. Future research could explore additional variables or consider different methodologies to further understand the complexities of job stress among healthcare professionals.